Gerakan 1000 Masker Melawan Corona: Pembagian di Kecamatan Denpasar Utara - Ni Wayan Ardiarani Utami; Kadek Risna Puspita Giri (LPPM Institut Desain dan Bisnis Bali, 2020)
The Coronavirus epidemic (Covid-19) which has infected the entire world has also arrived in Indonesia. Bali Province was not spared from this virus attack. Covid-19 Positive Cases in Denpasar City accounted for 31% of all positive cases in Bali Province. One of the recovered patients came from North Denpasar District, Peguyangan Kangin Village. The Central Government through the Ministry of Health of the Republic of Indonesia has issued a Circular Letter of the Minister of Health Republic of Indonesia concerning the Protocol to Prevent the Transmission of the Covid-19 virus, one of which is by using masks for people who leave their homes. This has caused STD Bali as a Design School to participate in preventing the transmission of the Covid-19 virus. STD Bali in Community Service activities carried out the